The Causes and Consequences of Early-Adult Unemployment: Evidence from Cohort Data - Andrew E. Clark; Anthony Lepinteur (Institute of Labor Economics (IZA), 2019)
We here use the employment-history data from the British Cohort Study to calculate an individual's total experience of unemployment from the time they left school up to age 30. We show that this experience is negatively correlated with the life satisfaction that the individual reports at age 30, so that past unemployment scars. We also identify the childhood circumstances and family background that predict this adult unemployment experience. Educational achievement and good behaviour at age 16 both reduce adult unemployment experience, and emotional health at age 16 is a particularly strong predictor of unemployment experience for women. Both boys and girls reproduce on average their parents' unemployment, so that adult unemployment experience is transmitted between generations. We uncover evidence of a social-norm effect: children from less-advantaged backgrounds both experience more adult unemployment but are less affected by it in well-being.
Keywords: J21; J63; I31; 330; unemployment; life satisfaction; habituation